2021
DOI: 10.3390/ijms22157882
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Promoting Effect of BMP Signaling in Endometrial Cancer

Abstract: The effects of bone morphogenetic proteins (BMPs), members of the transforming growth factor-β (TGF-β) family, in endometrial cancer (EC) have yet to be determined. In this study, we analyzed the TCGA and MSK-IMPACT datasets and investigated the effects of BMP2 and of TWSG1, a BMP antagonist, on Ishikawa EC cells. Frequent ACVR1 mutations and high mRNA expressions of BMP ligands and receptors were observed in EC patients of the TCGA and MSK-IMPACT datasets. Ishikawa cells secreted higher amounts of BMP2 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…High expression of BMP2 and BMP7 mRNA is associated with poorer survival in patients with endometrial cancer, albeit not significantly for BMP2 ( Fukuda et al, 2021 ). In addition, mutations in ACVR1, the gene encoding ALK2, are more frequently observed in endometrial cancer (>6%) than in most other cancers.…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 99%
See 3 more Smart Citations
“…High expression of BMP2 and BMP7 mRNA is associated with poorer survival in patients with endometrial cancer, albeit not significantly for BMP2 ( Fukuda et al, 2021 ). In addition, mutations in ACVR1, the gene encoding ALK2, are more frequently observed in endometrial cancer (>6%) than in most other cancers.…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 99%
“…However, how BMP signaling affects the progression of ACVR1 mutation-negative DIPG cells remains unknown. It should also be noted that mutations in the ACVR1 gene are observed in other types of cancers, including endometrial cancer, although the frequencies of the ACVR1 mutations are lower than those in DIPG ( Fukuda et al, 2021 ).…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, comparing the available evidence, we found that the four genes used to construct the EMTsig were closely related to EMT. BMP2 is a member of the TGFβ family and induces the process of EMT through the BMP signaling pathway ( Fukuda et al, 2021 ). SFRP2 is an upstream repressor of the WNT signaling pathway and has an inhibitory effect on the EMT process ( Duan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%